Effect of the molding temperature and cooling time on the residual stresses of crystal polystyrene (2014)
The use of crystal polystyrene for high performance components requires knowledge of the distribution of residual stresses. The aim of this research was to analyze the influence of the molding temperature and cooling time on the residual stresses present in parts of two types of crystal polystyrene PS1 and PS2, processed by injection molding. The results obtained using photoelasticity showed that at low temperatures the residual stresses increase due to the processes of formation and destruction of intermolecular forces. Internal stresses were reduced in the polymer specimens with greater thickness because the molecular relaxation of chains of polystyrene is facilitated by the space increase between the walls of the mold. It was concluded that the photoelasticity technique can be applied effectively in the measurement of residual stresses in injection molded crystal polystyrene parts.